The University of South Africa’s contributions to Lutheran theological training in higher education - James K. Mashabela (Verbum et Ecclesia)
The Evangelical Lutheran Church in Southern Africa (ELCSA) through its Oscarsberg Lutheran Theological College and Umphumulo Lutheran Theological College has been largely involved in the history of Lutheran theological training with the University of South Africa (Unisa). The ELCSA was very passionate to improve the quality of theological training and decided to further train their theological students at a university level. Oscarsberg Lutheran Theological College (OLTC) leadership started negotiations with Unisa for its theological students to be trained at Unisa.